"Importante Buhi!" the romanticization of Filipino resilience on social media in the wake of Typhoon Odette - Cabarubbias, Allane Angela D.; Moran, Jed Vincent O.; Nabua, Janna Rae D. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
This study examines the romanticization of Filipino resilience on social media in the wake of Typhoon Odette, and how this narrative affected the victims in terms of their personal experiences. Through this thesis, the researchers seek to address the lack of studies that highlight the extent to which Filipino resilience is romanticized on social media. Moreover, this study also aims to strengthen the existing body of information on the narrative of resiliency invoked during natural disasters by touching on the personal experiences of the typhoon victims themselves. Thus, this study utilizes the Media Dependency Theory to determine how Filipino resilience has been romanticized on social media in the wake of Typhoon Odette, and the Audience Reception Theory in grasping the victims? perceptions and views towards the narrative of Filipino resilience. In order to accomplish these objectives, the study applies the triangulation method through a content analysis of 7 social media posts, a survey disseminated to 100 respondents who were in Cebu during Typhoon Odette, and a focus group discussion with 10 participants taken from the survey, for the purpose of understanding the given communication phenomenon, that is, the public?s dependence on the media during natural disasters and the different ways of interpreting a message on social media.